Optimization of Healthy Life in Early Children During the Covid-19 Pandemic Time Through Education on Implementing Health Protocols, Balanced Nutrition, Clean and Healthy Living Behaviors - Elfina Yulidar; Sri Mujiyanti; Dini Rachmaniah (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The Covid-19 pandemic has made parents feel worried about looking after their sons and daughters. Various efforts have been made by parents to prevent their sons and daughters from contracting the virus. Education is a process of delivering educational material given to educational targets that aim to achieve behavior change. Education on the application of health protocols, the importance of balanced nutrition for children, and a clean and healthy lifestyle is certainly one of the efforts that can be made to break the chain of transmission and transmission of Covid-19 to children. These education providers increase knowledge about clean and healthy living behaviors for children and their families so that children can know what to do to prevent the chain of transmission of Covid-19. Optimization of healthy life in early childhood during the Covid-19 pandemic through education on the application of health protocols, balanced nutrition, and clean and healthy living behavior (PHBS) is carried out targeting early childhood. The educational activities were carried out in stages and the results of the process evaluation were carried out until the end of the activity according to the expected target, that is, early-age children can understand the importance of staying healthy by washing their hands, eating nutritious food and implementing health protocols wherever they are.